Bukkal mukozada lipom: vaka raporu - İsmail Şener; Emel Bulut; Mehmet Cihan Bereket; Akif Türer (Cumhuriyet University, 2012)
Lipomas are benign mesenchymal neoplasms composed of mature adipocytes, usually surrounded by a thin fibrous capsule. The most common location for lipomas in the maxillofacial region has been reported as the buccal mucosa and the peak incidence age for lipoma is 40 years and above. In the oral cavity, the most common sites are the cheek, tongue, palate, mandible and lip where lipomas occur as sessile or encapsulated masses. The present study reports a case of a 58-year-old man presented with a painless mass in the right vestibule that had been present for 6 months. The lesion was covered by normal mucosa, seemed to be circumscribed. Under local anesthesia, excision was performed. Histopathological examination was consistence with the diagnosis of a lipoma. Keywords: Lipoma, mature adipocytes, painless mass in vestibule.   ÖZET Lipomlar, çoğunlukla ince bir fibröz kapsül ile çevrili olgunlaşmış adipositlerden oluşan benign mezenşimal neoplazmlardır. Lipomlar en yoğun olarak 40  yaş ve üzerinde görülür. Maksilofasiyal bölgede en sık yerleştiği kısım bukkal mukoza olarak bildirilmiştir. Bunu sırasıyla dil, ağız tabanı, dudaklar izler. Oral kavitede lipomların en sık görüldüğü  bölgeler yanak, dil, damak, mandibula ve dudaktır ve genellikle sapsız ya da kapsüllü bir kitle olarak  gözlenirler. Bu olgu raporunda 6 aydır sağ alt vestibülde ağrısız şişliği bulunan, 58 yaşında erkek hasta sunulmuştur. Lezyon normal mukoza ile çevrili ve sınırlanmış olarak görülmekteydi. Hasta lokal anestezi altında opere edildi. Histopatolojik inceleme sonucunda lipom tanısı doğrulandı.